Meningkatkan Kualitas Lingkungan Perumahan Pada Masyarakat Penghuni Rumah Tipe Kecil di Kabupaten Soppeng - Muhammad Ardi; Faizal Amir; Bakhrani A. Rauf (Seminar Nasional LP2M UNM, 2019)
The purpose of this research is: 1) discovering knowledge, attitudes, motivation, and environmental behavior of small type household residents in Soppeng Regency before and after the experiment, (2) finding the effect of experiments on increasing knowledge, attitudes, observation, and environmental behavior of small type household residents in Soppeng Regency. This type of research is classified as experimental research which is located in a small type of housing complex in Soppeng Regency. The amount of sample are 25 households chosen by the random sampling method. The experimental design used is One Group Pretest-postest Design. The research variables are: (1) knowledge, attitude, motivation, and environmental behavior of small type household residents in Soppeng Regency, (2) the effect of experiments on increasing knowledge, attitude, motivation, and environmental behavior. The analysis used is: descriptive statistical analysis and statistical statistical analysis. The analysis model is the Dependent t-test. The results showed that: (1) knowledge, attitudes, motivation, and environmental behavior of small type household residents in Soppeng Regency before being trained were in the low category and after being trained were in the high category, (2) the effect of experiments on increasing knowledge, attitudes, motivation , and the environmental behavior of small type household residents in Soppeng Regency is very significant